Knowledge management in library organization - Muhamad Saufi Che Rusuli Dr (UMK Press, 2017)
Knowledge management (KM) is ana effort to increase useful knowledge in the library organization. This book discusses the scenario of KM in library perspectives, practices and approaches in librarian daily work. Numbers of case studies, theories and examples outlined that will inspire reader espacially academic librarians to practice and improve their level of understanding about KM practices in their own organizations. This book also gathers the wisdom of knowledge manager and researchers in the context of the university libraries and will be valuable reference source for all libraries.